2018
DOI: 10.1016/j.ejphar.2018.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of 7,8-dihydroxyflavone on neuropathological and neurochemical changes in a mouse model of Alzheimer's disease

Abstract: Interest in brain-derived neurotrophic factor (BDNF) was greatly enhanced when it was recognized that its expression is reduced in neurodegenerative disorders, especially in Alzheimer's disease (AD). BDNF signaling through the TrkB receptor has a central role in promoting synaptic transmission, synaptogenesis, and facilitating synaptic plasticity making the BDNF-TrkB signaling pathway an attractive candidate for targeted therapies. Here we investigated the early effect of the small molecule TrkB agonist, 7,8 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 61 publications
(88 reference statements)
0
28
0
1
Order By: Relevance
“…In addition, a higher level of tau protein has been confirmed as a marker of rapid cognitive decline, while the abundance of neurofibrillary tangles was correlated with the severity of dementia (33,34). Previous studies (20)(21)(22) investigated neurocognitive function of the 5xFAD mice, using an AD animal model with a Morris water maze assay. In addition, in a study performed by Kang et al (10) suggested that the levels of soluble Aβ are positively associated with the time awake and negatively associated with the time asleep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a higher level of tau protein has been confirmed as a marker of rapid cognitive decline, while the abundance of neurofibrillary tangles was correlated with the severity of dementia (33,34). Previous studies (20)(21)(22) investigated neurocognitive function of the 5xFAD mice, using an AD animal model with a Morris water maze assay. In addition, in a study performed by Kang et al (10) suggested that the levels of soluble Aβ are positively associated with the time awake and negatively associated with the time asleep.…”
Section: Discussionmentioning
confidence: 99%
“…The animals were acclimatized to the laboratory environment for 1 week before the experiments. The AD mouse model was constructed as previously described in which 1-year old 5xFAD mice spontaneously exhibit AD-like pathological changes (20)(21)(22), and mice received cerebral injection of Aβ 25-35 (cat. no.…”
Section: Methodsmentioning
confidence: 99%
“…In another related study using the fluid percussion injury (FPI) model, treatment with 7,8-DHF successfully restored TrkB signaling and memory function in the Barnes maze test [109]. 7,8-DHF also exhibited beneficial effects in the treatment of neurodegenerative diseases, including Alzheimer's disease (AD), Parkinson's disease (PD), Huntington's disease (HD), and amyotrophic lateral sclerosis (ALS) [110][111][112][113][114]. Recently, a derivative of 7,8-DHF, namely, BrAD-R13, was approved by the FDA for use in clinical trials for the treatment of mild to moderate AD.…”
Section: Improvement Of Bdnf Delivery and The Development Of New Trkbmentioning
confidence: 99%
“…The modulation of TrkB via small molecule drug formulations to enhance BDNF signaling also enhanced neuronal survival in degenerating neurons in vitro (Guerzoni et al, 2017) and improved motor function and motor neuron loss in ALS model mice (Korkmaz et al, 2014). BDNF potentiation has also been demonstrated to enhance MN survival in vitro (Tsai et al, 2013) and in other neurodegenerative diseases (Aytan et al, 2018). Additionally, transactivating TrkB by A 2 a receptors has also been reported to enhance survival of MNs in culture (Komaki et al, 2012).…”
Section: Detrimental Effects Of Bdnf/trkb In Alsmentioning
confidence: 99%